Pedagogi Dialogis Yesus dalam Yohanes 4: Fondasi Etika Biblis bagi Pendidikan Pembebasan yang Keberlanjutan - Bofry Wahyu Samosir (Fakultas Teologi, Universitas Sanata Dharma, 2026)
The dynamics of education in the 21st century still tend to be instrumental in nature, emphasizing only the transfer of knowledge and the preparation of workers for the market. As a result, this system fails to shape individuals into well-rounded human beings who have social and ecological responsibilities towards the world around them. This problem is also in line with Paulo Freire's criticism of the “banking concept of education,” which stifles critical consciousness. Faced with this problem, this article offers an alternative philosophy of education by recontextualizing the pedagogy of Jesus Christ in John 4 as a liberating and restorative educational paradigm. Specifically, through a hermeneutical approach, this article argues that Jesus' pedagogy, based on Christology Λόγος (Word), systematically breaks down the walls of gender and ethnic marginalization. The uniqueness of Jesus' dialogue with the Samaritan woman not only frees her from the shackles of social and religious marginalization as imago Dei, but also transforms her into an active agent of change. For the author, this process of personal liberation is an ethical prerequisite for the realization of personal responsibility towards others and nature. Thus, this article concludes that Jesus' dialogical pedagogy in John 4 is an ethical imperative that provides a biblical foundation for developing a framework of liberation education, leading to holistic sustainability practices. Therefore, as a form of contextualization, this pedagogical model provides a roadmap for educators, theologians, and ecologists to build collaborative networks in realizing concrete, sustainable, and just actions at the community level.AbstrakDinamika Pendidikan di abad ke-21 masih cenderung bersifat paradigma instrumental yaitu memberikan penekanan hanya pada aspek transfer pengetahuan, dan penyiapan tenaga kerja untuk pasar. Akibatnya sistem ini gagal membentuk setiap pribadi menjadi manusia utuh yang memiliki tanggung jawab secara sosial dan ekologis terhadap dunia di sekitarnya. Permasalahan ini juga sejalan dengan kritik Paulo Freire terhadap